Miopía astigmática y queratocono en paciente femenina de 29 años - Aguilar Aguilar, Jefferson Alejandro (2021)
Visual health can be affected by various pathologies, among them is keratoconus which is degenerative, once detected it is necessary to implement adequate treatment, specifying to the patient that if he does not comply with his treatment the consequences could be loss of vision. The optometrist professional must provide primary care to patients who come for consultation to provide an adequate diagnosis. The present case study is of a 29-year-old female patient with astigmatic myopia and keratoconus who presents with distant vision loss despite having visual correction. Methodology: an analysis of the patient's data, clinical history and analysis of the tests performed was carried out. Results: the patient indicates that she wears contact and frame lenses according to her activities. He indicates that he was detected myopia at the age of 12 and has been wearing glasses since then. He states that an assessment should be carried out every 6 months but due to labor issues he omitted the procedure. His last check-up was two years ago, that is, before the pandemic. Retinoscopy was performed and scissor reflexes, a sign of possible keratoconus, were detected. Conclusions: The patient suffers from astigmatic myopia and development of photosensitivity, decreased visual quality, a principle of keratoconus is detected, she is referred to the ophthalmologist to carry out complementary studies to rule it out or establish an adequate diagnosis.